Paraphenylenediamine (PPD) Poisoning: A Case with a Fatal Outcome - Attia Khaliq; Rashid, Amir; Karamat Ali; Laila Yaseen (Pakistan Armed Forces Medical Journal, 2024)
In developing countries, people use Paraphenylenediamine, a highly toxic substance, for suicide and self-harm. It is more common in populations with lower socioeconomic classes and educational backgrounds. The female-to-male ratio is higher. The most common complications are oedema of the upper airway tract and renal failure. The mortality rate is higher due to late hospital presentation and a lack of specific antidotes. The treatment of Paraphenylenediamin poisoning is conservative. In this case report we are presenting Paraphenylenediamine poisoning with a fatal outcome.